Consumer Behavior Analysis of Islamic Financial and Banking Institutions - Hatta, Achmad; Amarul, Amarul; Supriatna, Yuda (Universitas Serang Raya, 2023)
This study aims to determine the problems that exist in consumer behavior in Islamic financial and banking institutions. To find out this, a research was conducted on consumer behavior especially at Islamic Banks. This study uses a qualitative approach using secondary data. The results of the analysis show that there are several consumers behavior problems related with their intention and interest towards Islamic banks namely: religious/beliefs, culture factor and social factors, personal factors, psychology, motivation, perception, learning process, attitudes, ease and speed of processing, location and physical attributes, price, employee service.